On the Magnetic Braking Law in Black Hole Low-mass X-Ray Binaries - Deng, Zhu-Ling; Li, Xiang-Dong (The Astrophysical journal, 2024)
Magnetic braking (MB) plays an important role in the evolution of close low-mass X-ray binaries (LMXBs). It is also essential to the formation of ultracompact X-ray binaries (UCXBs). There have been lively investigations on the MB mechanism(s) in both single stars and close binaries including cataclysmic variables and neutron star (NS) LMXBs but with diverse conclusions. In this paper we explore the effect of MB on the black hole (BH) LMXB evolution. We combine binary population synthesis with detailed binary evolution to obtain the expected properties of the Galactic BH LMXB population. The simulated results are compared with the observational data including the BH mass, companion mass, companion temperature, orbital period, and mean accretion rate. Our results reveal that the MB laws with relatively low efficiency (i.e., RM12 and RVJ83) exhibit better agreement with observations, contrary to what was found for NS LMXBs. This raises the interesting question about whether MB really follows the same unified law in different types of binaries. We also predict that only a very small fraction (≲2.5%) of BH LMXBs can evolve to be UCXBs. This explains why no BH UCXB has been discovered so far.